All-around management of a fungal isolate obtained from cheese spoilage as an environmental source: direct approach from an undergrad student to a biotechnological characterization - Ortiz Lechuga, Eugenia Guadalupe; Tovar Herrera, Omar Eduardo; Arévalo Niño, Katiushka (Elsevier, 2019)
In this work, we present the results of an undergrad student from the perspective of its first approach as a principal researcher in a project. In order to gain practical experience, one of the options for students that have interest in pursuing a postgraduate programcorresponds to aresearchstay in a laboratory of their selected field conducting a project for a period of 6 months. Inthisparticular project,a fungal samplewasisolated from Parmesan cheese spoilage and its enzymatic activity evaluated. Using simple and standardized protocols, the student was capable of identifying a possible biotechnological application for the isolate by detecting and categorizing the lipolytic activity. Through microculture characterization in potato dextrose agar (PDA) the genus of the sample was determined as Penicillium and confirmed by molecular analysis of the ITS1 and ITS4 regions. In order to examine comprehensively the potential of the new isolate, the extracellular and intracelular enzymaticactivitieswereanalyzedaswellasfourmethodsof cell rupture. From these results, sonication was determined as the best technique with 211 U/L as a maximum lipolytic value. Tofinalize the evaluation of the sample, the student determined the optimal pH and temperature as well as the thermotolerance of the crude extract obtaining a residual activity of 13% after 60 minutes of incubation at 45 C. Upon conclusion of the research we could recognize that through a direct characterization of a fungal isolate using techniques that are widely known, the student was capable of determining and value one of the most interesting capabilities fungi has to offer; enzymatic activity, and that the knowledge obtained fromestablished protocols enables and encourages the students to correlate the source from where they were obtained with potential biotechnological applications